(untitled) (European Journal of Health Research, 2015)
Introduction: Healthcare professionals daily perform labors of personal care which impact on their quality of life and affect them to the point of burnout. Its prevalence is increasing and for it to exist, both job pressure and individual stress have to interact. Purpose: To review the literature published on burnout in healthcare personnel in the last 15 years, and analyze the factors that have influenced these studies. Methodology: To carry out this study, a systematic search was made in two databases, Psicodoc and Dialnet. The keywords used in the search were “Burnout in caregivers” and “burnout in healthcare workers”, and the search was limited to publications from 2000 to 2015. A total of 16 articles were selected for review and 47 articles were discarded because they did not meet the criteria for inclusion. Results: The results of this review show that the risk factors that increase or decrease burnout scores are workplace, sex, professional category, and area of work. Conclusions: This study shows that the prevalence of burnout in healthcare personnel depends on a series of factors that have to be associated to consider a person to be suffering from burnout.